Conflicting agendas: evaluating feminist programmes for women offenders - Shaw, Margaret (1997)
This thesis is concerned with the central rationale of feminism, and thus of feminist perspectives in criminology, to bring about change for women subject to the criminal justice system. It argues that any attempt to influence that system, to bring about change or reform, must be considered within the broader context of policy-making and programme development and their underlying assumptions and purposes, as we]] as in relation to specific contextually located histories. It does so by tracing the history of a particular feminist initiative in Canada - a community-based programme in Nova Scotia which offered feminist therapy and counselling to women in conflict with the law. It traces the processes of funding and evaluation for the federal government, and the differential experiences of the project and its clients, the researchers, and the funders.